2021
DOI: 10.1177/11782218211033298
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alcohol Habits Among Workers During the Confinement of COVID-19: Results of a Canadian Cross-Sectional Survey

Abstract: Background: The restrictions implemented around the world to contain the spread of the coronavirus disease 2019 (COVID-19) impact workers. Emotional distress and maladaptive behaviors such as alcohol misuse are expected, particularly in vulnerable groups such as front-line health workers. In the present study, we examined if alcohol consumption behaviors in Quebec workers changed during confinement of the COVID-19 pandemic, and whether healthcare workers reported specific patterns of changes. Methods: Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
4
7
0
Order By: Relevance
“…Conversely, reduced hours in response to the shut down or reduction of clinical areas were also described as drivers of change to alcohol consumption. These findings mirror those found across the general population, particularly during lockdowns (Mongeau‐Pérusse et al, 2021 ; Sallie et al, 2020 ). Alcohol consumption has been shown to have a direct impact on personal well‐being (Parackal & Parackal, 2016 ), with heavy alcohol use shown to increase the susceptibility to burnout and absenteeism (Ahola et al, 2006 ; Cunradi et al, 2005 ; Fagin et al, 1996 ; Pedersen et al, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
“…Conversely, reduced hours in response to the shut down or reduction of clinical areas were also described as drivers of change to alcohol consumption. These findings mirror those found across the general population, particularly during lockdowns (Mongeau‐Pérusse et al, 2021 ; Sallie et al, 2020 ). Alcohol consumption has been shown to have a direct impact on personal well‐being (Parackal & Parackal, 2016 ), with heavy alcohol use shown to increase the susceptibility to burnout and absenteeism (Ahola et al, 2006 ; Cunradi et al, 2005 ; Fagin et al, 1996 ; Pedersen et al, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
“…Thompson (2000 adults, 51.9% females) found that while females reported higher rates of emotional distress, significant associations with increased drinking frequency were only observed among males in gender-stratified analyses ( 42 ). On the contrary, Mongeau-Pérusse ( 43 ) found an increase in alcohol use in 847 participants (77.8% of females).…”
Section: Discussionmentioning
confidence: 92%
“…Emerging literature during the SARS-CoV-2 pandemic indicates that mental health concerns (including alcohol/substance use) have worsened for HCWs and PSP (Hall, 2020 ; Mehta et al, 2022 ; Mongeau-Pérusse et al, 2021 ; Pestana et al, 2022 ; Robles et al, 2021 ; Saragih et al, 2021 ; Turna et al, 2022 ; Young et al, 2021 ), with the number of healthcare visits by HCWs for mental health and substance use problems also increasing throughout (Myran et al, 2022 ). Based on a recent meta-analysis, the global prevalence rate of PTSD among HCWs during the pandemic is estimated to be 49% (Saragih et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, comparing mental health concerns among HCWs in Canada, Brazil, and the USA, Canadian HCWs reported the highest rates of anxiety, depression, and increased alcohol and cannabis use compared to their international counterparts (Turna et al, 2022 ). In a nationwide cohort study, Canadian HCWs reported increased alcohol consumption compared to pre-pandemic (Mongeau-Pérusse et al, 2021 ). To our knowledge, no literature has examined prevalence rates of PTSD and alcohol/substance use among Canadian PSP during the pandemic underscoring the need to further study this occupational group.…”
Section: Introductionmentioning
confidence: 99%